2021
DOI: 10.7554/elife.67097
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing eflornithine to treat a patient with a rare ODC1 gain-of-function variant disease

Abstract: Background:Polyamine levels are intricately controlled by biosynthetic, catabolic enzymes and antizymes. The complexity suggests that minute alterations in levels lead to profound abnormalities. We described the therapeutic course for a rare syndrome diagnosed by whole exome sequencing caused by gain-of-function variants in the C-terminus of ornithine decarboxylase (ODC), characterized by neurological deficits and alopecia.Methods:N-acetylputrescine levels with other metabolites were measured using ultra-perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…Additional support may be required for more severely affected patients. As more is known about treatment with DFMO, the natural history of neurocognitive findings in this syndrome may change (Rajasekaran et al, 2021 ). Diagnoses like autism spectrum disorder (ASD) and intellectual disability (ID) may become more apparent as cognitive and behavioral development progresses functionality to the level of being able to make that diagnosis with more confidence.…”
Section: Discussionmentioning
confidence: 99%
“…Additional support may be required for more severely affected patients. As more is known about treatment with DFMO, the natural history of neurocognitive findings in this syndrome may change (Rajasekaran et al, 2021 ). Diagnoses like autism spectrum disorder (ASD) and intellectual disability (ID) may become more apparent as cognitive and behavioral development progresses functionality to the level of being able to make that diagnosis with more confidence.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, DFMO is clinically approved for the treatment of African trypanosomiasis (41), and its use as a maintenance therapy for pediatric neuroblastoma patients has provided valuable data on safety and administration (42,43). DFMO has a decades-long history of safe administration in clinical trials and has recently been repurposed to treat patients with Bachmann-Bupp syndrome (BABS), a newly identified genetic disorder resulting from an ODC gain-of-function variant (44,45). The presentation of BABS emulates that of SRS in several aspects, including developmental delay, hypotonia, dysmorphic features, and non-specific brain MRI findings (46), most of which dramatically improved with DFMO treatment (44).…”
Section: Discussionmentioning
confidence: 99%
“…DFMO has a decades-long history of safe administration in clinical trials and has recently been repurposed to treat patients with Bachmann-Bupp syndrome (BABS), a newly identified genetic disorder resulting from an ODC gain-of-function variant (44,45). The presentation of BABS emulates that of SRS in several aspects, including developmental delay, hypotonia, dysmorphic features, and non-specific brain MRI findings (46), most of which dramatically improved with DFMO treatment (44). Our studies in SRS patient-derived cell lines indicate that DFMO effectively reverses the aberrantly elevated SPD/SPM ratio that is the main biochemical hallmark of SRS.…”
Section: Discussionmentioning
confidence: 99%
“…ODC gain-of-function mutations have been associated with hyper-proliferative diseases, including cancer, infections, overgrowth, neural overproliferation, and the ODC-linked neurodevelopmental disorder, Bachmann–Bupp syndrome. Recently, Prokop et al have identified ODC G84R as a variant associated with intellectual disability and seizures. Activity assays using recombinant ODC indicated that G84R is a loss-of-function mutation, and the authors hypothesized that ODC partial loss-of-function may lead to neural depletion .…”
Section: Discussionmentioning
confidence: 99%